Effects of Dexamethazone on the Blood Sugar Level of Patients Under General Anesthesia: Systematic Review - Y Sultan, Ayman Hussian; Mahmoud M Wali, Musaab; H Alturi, Faisal Mohammed; I Alshareef, Faisal Yousif; M Aldahlawi, Badr Mohammedshaker (Journal of Neonatal Surgery, 2025)
Introduction: Dexamethasone is a commonly used medication for the prevention of Postoperative Nausea and Vomiting (PONV) in patients who receive general anesthesia. But its glucocorticoid effects result in hepatic gluconeogenesis and peripheral insulin resistance, causing concerns about the potential for perioperative hyperglycemia. In Saudi Arabia, where the world's highest prevalence of Type 2 Diabetes Mellitus is reported, it is important to better understand the metabolic effects of this single-dose steroid to ensure patient safety and improve surgical outcomes. Objective: The aim of this systematic review is to assess the magnitude and duration of hyperglycemia after using intraoperative dexamethasone. The aim is to establish the magnitude of the blood glucose rise with varying doses (4 mg and 8 mg) and to compare the response in diabetic versus non-diabetic patients. Methods: A systematic review complied with PRISMA guidelines. We searched several databases (PubMed, Cochrane Library and the Saudi Medical Journal) to find Randomized Controlled Trials (RCTs) that included adult patients under general anesthesia. The studies were required to compare the intravenous administration of dexamethasone to a placebo, with blood glucose measurements taken at 0, 2, 4, 8, 12 and 24 hours. We combined the data using a random effects model to calculate the mean change in glucose level. Conclusion: This review shows that dexamethasone causes a statistically significant but short-lived rise in blood glucose, with peak effects occurring 4-8 hours after induction. Although the elevation (average 15-35 mg/dL) is clinically tolerable in non-diabetic patients, there are greater variations in patients with diabetes. However, there is no evidence of increased surgical site infections. The review concludes that dexamethasone can be safely used in clinical practice in Saudi Arabia if a risk-stratified approach, involving lower doses and HbA1c levels, is taken to manage patients with high risk of metabolic stress.